1995
DOI: 10.1002/art.1780381119
|View full text |Cite
|
Sign up to set email alerts
|

Antibody reactivity to the hres‐1 endogenous retroviral element identifies a subset of patients with systemic lupus erythematosus and overlap syndromes

Abstract: Objective. To evaluate the correlation between the presence of antibodies to an endogenous retroviral element-encoded nuclear protein autoantigen, HRES-1, and the presence of other antinuclear antibodies and HLA class I1 alleles in patients with systemic lupus erythematosus (SLE) and overlap syndromes.Methods. Antibody reactivities to native and recombinant proteins and synthetic peptides were assessed by counterimmunoelectrophoresis, enzyme-linked immunosorbent assay, and Western blotting. HLA class I1 allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 52 publications
0
59
0
Order By: Relevance
“…HRES-1 is a transcriptionally active HERV that encodes a 28 kDa nuclear autoantigen, HRES-1/p28 and a small GTP-ase, HRES-1/Rab4. Autoantibodies to HRES-1/p28, which are found in half of the patients with SLE [23][24][25][26][27], are cross-reactive with antigens of viruses infecting patients with SLE, such as TTV and EBV [71] and the 70 kDa component of U1 snRNP [24] and may thus contribute to epitope spreading and development of anti-nuclear antibody (ANA). In turn, HRES-1/Rab4 regulates the recycling of CD4, a key component of the IS, which is abnormally assembled in T cells of patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HRES-1 is a transcriptionally active HERV that encodes a 28 kDa nuclear autoantigen, HRES-1/p28 and a small GTP-ase, HRES-1/Rab4. Autoantibodies to HRES-1/p28, which are found in half of the patients with SLE [23][24][25][26][27], are cross-reactive with antigens of viruses infecting patients with SLE, such as TTV and EBV [71] and the 70 kDa component of U1 snRNP [24] and may thus contribute to epitope spreading and development of anti-nuclear antibody (ANA). In turn, HRES-1/Rab4 regulates the recycling of CD4, a key component of the IS, which is abnormally assembled in T cells of patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, higher expression levels in SLE lymphocytes correlate with production of U1 snRNP [57] which includes a 70 kDa protein with a region of homology to gag antigens of infectious and ERV [24,58]. The 1q42 chromosomal region that has been associated with lupus susceptibility [59] and harbors the HRES-1 ERV [27,60] is genetically unstable [61].…”
Section: Activation Of Erv By Dna Demethylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In lupus patients, however, antibody levels to human immunodefi ciency virus type I p24 gag proteins are increased, and endogenous retroviruses are found in sera [65][66][67] . Two studies [66,67] showed a correlation between these antibodies and specifi c antibodies and clinical features (e.g., severe discoid LE). Nevertheless, despite a large number of studies, there is as yet no conclusive evidence to support the direct linkage of LE to endogenous or exogenous retroviruses in humans.…”
Section: Viruses and Other Infectious Agentsmentioning
confidence: 99%
“…Polyclonal antibodies revealed a 28-kDa protein concordant with the predicted molecular weight of the p25 protein. This product was related to the HRES-1 gag ORF (11).The serum antibody reactivity against the 2 HRES-1 peptides was tested, and the GAG p24 HTLV-1 reactivity, previously observed in autoimmune patient's sera, was subsequently related to anti-HRES-1 antibodies (11)(12)(13).…”
mentioning
confidence: 99%